Consumer acceptance towards innovation in Malay traditional food - Cerlina Sali; Mohammad Yunus Mohd Noor Azni; Najwa Che Supian; Nasirahtul Akmar Kamarudin (2022)
The study examines consumer acceptance toward innovation in Malay traditional food and to find out the relationship between attitude, perceived authenticity, and perception of consumer acceptance. A survey was conducted using questionnaires, involving 384 respondents who consume Malay traditional food. Descriptive and correlation analyses were used to analyze the data obtained. Findings revealed that the three variables are significantly related to consumer acceptance attitude showed the strongest relationship while perception showed the weakest relationship with consumer acceptance. Implications and recommendations were provided for future researchers in line with the study.